Family climate influences next-generation family business leader effectiveness and work engagement - Miller, Stephen P. (Frontiers in Psychology, 2023)
Effective next-generation leadership is central to the success of family businesses through multiple generations of family ownership. This study of 100 next-generation family business leaders found that open and transparent communication in the family positively influences the expression of emotional and social intelligence competencies in their leadership behaviors, which in turn drives their leadership effectiveness. Open communication in the family also makes it more likely next-generation leaders will be held accountable for their leadership performance by others, which increases the degree to which they derive energy, inspiration, and fulfillment from their work in the family firm. On the other hand, the results suggest that senior-generation family leaders who exercise unquestioned authority and set all the rules, an autocratic leadership style common among entrepreneurs who found family firms, make it less likely that next-generation family leaders will learn the emotional and social intelligence competencies that predict their leadership effectiveness. The study also found that autocratic senior-generation leaders negatively affect next-generation leader self-efficacy and make it less likely that others will hold them accountable, which limits their engagement with work in the family business. The study’s most important finding is that the degree to which next-generation leaders accept personal responsibility for their actions and decisions serves as a mediator through which the nature of the family climate influences their leadership effectiveness and work engagement. This suggests that while the nature of family relationships may make it easier or more difficult, next gens have ultimate control over the development of their leadership talent and positive engagement with work in or outside of the family business.